Impact of landscape management scenarios on ecosystem service values in Central Ethiopia - Biratu, Abera Assefa; Bedadi, Bobe; Gebreyohannis, Solomon Gebrehiwot; Melesse, Assefa M.; Nebi, Tilahun Hordofa; Abera, Wuletawu; Tamene, Lulseged D.; Egeru, Anthony (MDPI, 2022)
This study aimed at modeling scenarios of future land use and land cover (LULC) change and estimating ecosystem service (ES) values for the year 2051 compared to 2021 in Central Ethiopia. The future LULC changes for the year 2051 were simulated for four scenarios, namely Business-as-Usual (BAU), Rapid Agricultural Expansion (RAE), Ecosystems Protection and Agricultural Development (EPAD) and Landscape Ecosystems Restoration and Conservation (LERC). The four LULC change scenarios were simulated based on anticipated assumptions that were derived from existing spatial policies, a consultation workshop report on scenarios of agricultural development in Ethiopia, suitability analysis, population growth analysis and expert knowledge of the study area characteristics. We used a Multi-Layer Perceptron–Artificial Neuron Network (MLP–ANN) model-based projected LULC for the BAU scenario and the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model to generate RAE, EPAD and LERC scenarios in the study landscape. The benefit transfer method was used to estimate the total ES values and for trade-off analysis. The result showed that LULC changes in the study area varied across simulated scenarios compared to the base year 2021. Under the BAU and RAE scenarios, cultivated land increased by 146,548 ha (22%) and 193,965 ha (29%), whereas forest, water body, wetland and shrub-bush land were reduced. However, forest cover increased by 31,725 ha and 100,080 ha but bare land was reduced by 8466 ha (21%) and 10,379 ha (25%) under the EPAD and LERC scenarios. The forest cover annual rate of change was 3.2% and 6% under the EPAD and LERC scenarios. As a result, the total ES value increased by USD 24.5 and 78.5 million under the EPAD and LERC scenarios for the year 2051, whereas the total ES value was reduced under the BAU and RAE scenarios by USD 27.1 and 73.2 million. The trade-offs among ecosystem services were significantly synergized under the LERC scenario compared to RAE. Therefore, EPAD and LERC could be used as a reference for sustainable landscape planning and management. Landscape ecosystems restoration integrated with a sustainable agricultural intensification approach would enable us to ensure the sustainability of both agricultural production and ecosystem service synergies without negatively affecting the natural environment.